CRITICAL REVIEW OF ETHICAL CONSIDERATIONS IN EMERGENCY HEALTHCARE IN BALANCING PATIENT AUTONOMY, RESOURCE ALLOCATION, AND PROFESSIONAL RESPONSIBILITIES - 1Abdullah Hussain Alajabi, 2Saleh Hussain Ali Alyami, 3Abdullah HadiMesfer Al Moreh, 4Abdullah Hassan Salem Alsaiary, 5Mansour Abdullah Mansour Alhaydar, 6Mohammed Yahya Jamesh, 7Duayrim Yahya DuayrimAlhareth, 8Omar Hussain Muhammad Alajabi, (Chelonian Research Foundation, 2022)
Emergency healthcare presents complex ethical dilemmas, requiring a delicate balance between patient autonomy, resource allocation, and professional responsibilities. This essential survey investigates moral contemplations in crisis healthcare and the challenges and results of reacting to these challenges. By investigating existing writing, this ponders various moral issues, composition quality, and world occasions to understand the complexity of problem-solving choices. Utilize charts, words, and pictures to demonstrate key points and discoveries. This comes about by understanding the moral nature of risky drugs and offering suggestions for the moral treatment of this imperative issue. Keywords: Emergency healthcare, ethics, patient autonomy, resource allocation, professional responsibilities.